Atypical CLN2 with later onset and prolonged course: a neuropathologic study showing different sensitivity of neuronal subpopulations to TPP1 deficiency - Elleder, Milan; Dvořáková, Lenka; Stolnaja, Larisa; Vlášková, Hana; Hůlková, Helena; Druga, Rastislav; Poupětová, Helena; Košťálová, Eva; Mikuláštík, Josef (Acta neuropathologica, 2008)
This is the first neuropathology report of a male patient (born 1960-died 1975) with an extremely rare, atypical variant of CLN2 that has been diagnosed only in five families so far. The clinical history started during his preschool years with relatively mild motor and psychological difficulties, but with normal intellect and vision. Since age six there were progressive cerebellar and extrapyramidal symptomatology, amaurosis, and mental deterioration. Epileptic seizures were absent. The child died aged 15 years in extreme cachexy. Neuropathology revealed neurolysosomal storage of autofluorescent, curvilinear and subunit c of mitochondrial ATP synthase (SCMAS) rich material. The neuronal storage led to laminar neuronal depopulation in the cerebral cortex and to a practically total eradication of the cerebellar cortical neurons. The other areas of the central nervous system including hippocampus, which are usually heavily affected in classical forms of CLN2, displayed either a lesser degree or absence of neuronal storage, or storage without significant neuronal loss. Transformation of the stored material to the spheroid like perikaryal inclusions was rudimentary. The follow-up, after 30 years, showed heterozygous values of TPP1 (tripeptidylpeptidase 1) activity in the white blood cells of both parents and the sister. DNA analysis of CLN2 gene identified a paternal frequent null mutation c.622C > T (p.Arg208 X) in the 6th exon and a maternal novel mutation c.1439 T > G in exon 12 (p.Val480Gly). TPP1 immunohistochemistry using a specific antibody gave negative results in the brain and other organs. Our report supports the notion that the spectrum of CLN2 phenotypes may be surprisingly broad. The study revealed variable sensitivities in neuronal subpopulations to the metabolic defect which may be responsible for the variant's serious course.
Keywords: aminopeptidasy; Aminopeptidases; buněčná inkluze; progrese nemoci; Brain; Adolescent; Serine Endopeptidases; neurony; mužské pohlaví; mladiství; mitochondriální protonové ATPasy; Financing, Organized; neuronální ceroidlipofuscinózy; Humans; Child, Preschool; Neurons; Mitochondrial Proton-Translocating ATPases; lidé; serinové endopeptidasy; mozek; Endopeptidases; Neuronal Ceroid-Lipofuscinoses; Child; endopeptidasy; Inclusion Bodies; Age of Onset; Disease Progression; financování organizované; předškolní dítě; dítě; Male; věk při počátku nemoci